Motivational interviewing in nutrition and fitness - Clifford, Dawn (Applications of motivational interviewing, 2016)
"Making and maintaining lasting changes in nutrition and fitness is not easy for anyone. Yet the communication style of a health professional can make a huge difference. This book presents the proven counseling approach known as motivational interviewing (MI) and shows exactly how to use it in day-to-day interactions with clients. MI offers simple yet powerful tools for helping clients work through ambivalence